Relevansi Kurikulum Merdeka Dengan Konsepsi Ki Hadjar Dewantara: Studi Kritis Dalam Perspektif Filosofis-Pedagogis - Pitri Maharani Efendi; Tatang Muhtar; Yusuf Tri Herlambang (Elementary Teacher Education Program, Majalengka University, 2023)
ABSTRACT This study aims to explore the scope of the independent curriculum, Ki Hadjar Dewantara's conception, and the relevance of the independent curriculum to Ki Hadjar Dewantara's conception based on critical studies in a philosophical-pedagogical perspective. The independent curriculum is a policy program in the field of education that emphasizes giving freedom to schools including teachers and students to innovate and learn independently. The background of this study is to analyze the alignment between the independent curriculum itself and Ki Hadjar Dewantara's conception. The research method used is literature study. The stages carried out in this literature study are 1) choosing the source material that comes from journals; 2) browse the reference literature; 3) reading references; 4) write notes; and 5) present the results of the journal review. Based on the study of the journal, the results show that there is relevance and interrelationship between the independent curriculum and Ki Hadjar Dewantara's conception of education from a philosophical and pedagogical perspective. So it can be concluded that the independent learning curriculum concept is relevant to the conception of education initiated by Ki Hadjar Dewantara where the principle of independence is very important for students so that the concept of acquiring learning is not only in the process of imparting knowledge to students, but students are given the freedom to develop independently but with teacher supervision. along with parents.